Roles of Clinical Features and Chest CT in Predicting the Outcomes of Hospitalized Patients with COVID-19 Developing AKI (Iranian Journal of Kidney Diseases, 2023)
This research aimed to evaluate the clinical features and computed tomography (CT) scans associated with poor outcomes in COVID-19 patients with acute kidney injury (AKI). A total of 351 COVID-19 patients (100 AKI, 251 non-AKI) hospitalized at Imam Hossein Teaching Hospital affiliated to Shahid Beheshti University of Medical Sciences were included. To investigate the factors associated with in-hospital mortality in COVID-19 patients developing AKI, COX univariate and multivariate regression models were applied after controlling other confounding variables. C-reactive protein CRP, lactate, and procalcitonin levels were significantly higher in AKI patients than in non-AKI patients (P < .05). In addition, AKI patients had higher frequencies of lymphopenia and leukocytosis (P < .05). The troponin levels and WBC were the most significant factors for predicting mortality in patients with AKI. Our findings showed that AKI per se is much more important than any other prognostic factor affecting non-AKI patients. However, AKI patients with higher CRP, PCT, and lactate levels had a poor prognosis.  DOI: 10.52547/ijkd.7241